A survey on current management of patients with mild (Stage 1) hypertension by physicians in Metro Cebu towards the formulation of practice guidelines - Quiza, Ma. Fidelis E.
Because over 90 of hypertensive patients are in the mild to moderate range with 50 classified as having mild or Stage I Hypertension, this group of patients accounts for a major proportion of the excess risk in terms of morbidity, disability and mortality attributable to hypertension. Despite the disproportionately larger risk for the population at large from Stage I Hypertension, therapy of all patients with Stage I Hypertension is only marginally cost effective relative to treatment of patients with Stage 2 - Stage 4 Hypertension.To describe the current practices and the determinants to the various practice patterns in the management of patients with mild or Stage I Hypertension and compare these with standards recommended in literature.All licensed physicians who have been in active practice since at least 1992 to the present time of the conduct of the survey regardless of type of practice, or affiliation and who actively manage adult patients with hypertension in Metro Cebu.A structured questionnaire was formulated based on focus group discussions and hypertension consensus guideline recommendations. After pre-testing, the 31-item questionnaire was delivered to identified subjects in Metro Cebu.Main outcome meausres (1) Case definition, evaluation, treatment and follow-up of patients with Stage I Hypertension, (2) drug utilization patterns in the management of patients with Stage I Hypertension, (3) determinants to the selection of interventional strategies (4) physician's rating of the adequacy of control of Stage I Hypertension in their respective practices, (5) deviant practice patterns based on JNC VI and Philippine Multisectoral Task Force guidelines (6) perceived barriers to adequacy of hypertension control as reported by the respondents and descriptive statistics using measures of central tendency and dispersion for continuous variables and frequency or proportion for categorial variables. Univariate analysis used to determine significant relationships between physician-related independent variables and practice patterns or to explain differences in outcome were carried out using the Chi-Square test for categorial variables and the nonparametric tests such as Mann-Whitney-U Test and the Kruskall Wallis 1-Way ANOVA for continuous variables. A logistic regression analysis using forward selection with likelihood-ratio criterion was done to determine for significant relationships between variables entered as covariates.A total of 354 questionnaires were sent and 228 returned forms were analyzed for a total response rate of 64.4.The questionnaire took 35.7 +-8.2 minutes to complete. Clinic prevalence of hypertension ranged from less than 10 to 40. Stage I Hypertension prevalence was up to 60 of total hypertension seen in practice. BP control was judge adequate for at most 30 of patients with hypertension. Some respondents claimed adequate control in less than 10 of patients with Stage I Hypertension, whereas other respondents claim adequate control in 80 -90 of the same group of patients. A difference in response was attributed to a difference in the type of practice area of specialization.Majority of the respondents correctly defined 140 mm Hg and 90 mm Hg as the lower limits of systolic and diastolic BP, respectively for Stage I Hypertension.